A contextual approach to the interpretation of the early Bronze Age skeletons of the East Anglian Fens - Lillie, Malcolm C.
The fenland peats of eastern England have produced some 36 prehistoric burials, whose distinctive associations place them into the early Bronze AgeÐjust sufficient for pattern to be evident in their placing and character.